Diagnostic performance of flexible sigmoidoscopy combined with fecal immunochemical test in colorectal cancer screening: meta-analysis and modeling - Niedermaier, Tobias; Brenner, Hermann (European journal of epidemiology, 2017)
Once-only flexible sigmoidoscopy (FS), which reliably detects neoplasms in the distal colon and rectum but not in the proximal colon, has been shown to reduce incidence and mortality of distal colorectal cancer (CRC). Fecal immunochemical tests (FITs) detect the majority of CRCs and some proportion of adenomas also in the proximal colon. We assessed the expected diagnostic performance of combined application of FS and FIT. We systematically reviewed screening studies conducted in an average risk population that reported specificities and site-specific sensitivities of FITs for detection of CRC or advanced adenoma (AA). Only studies that conducted colonoscopy in all subjects were included. PubMed and Web of Science were searched until May 13, 2016. Reference lists of eligible studies were also screened. Sensitivity of FS was derived from colonoscopy results, assuming the same sensitivity as colonoscopy for left-sided neoplasms and follow-up colonoscopy after detection of distal adenomas. Bivariate meta-analyses were used to derive summary estimates of overall sensitivity and specificity of individual and joint application of both tests. Ten eligible studies were identified. Summary estimates (95% confidence intervals) of overall sensitivity for detecting CRC and AA were 65% (56-74%) and 27% (23-31%) for FIT alone, 67% (58-75%) and 67% (59-75%) for FS alone, and 89% (83-92%) and 75% (68-80%), respectively, for the combination of both tests. The pooled specificity (95% CI) of FIT was 92% (90-95%). Adding a FIT to a once-only screening FS would substantially increase sensitivity of CRC screening at a modest loss in specificity.